Discovery of a Novel Series of Tetrahydro‐β‐carbolines Inducing Autophagic Cell Death in Human Metastatic Melanoma. Issue 6 (20th March 2014) - Ahmed, Nermin S.; Elgendy, Mohamed; Laufer, Stefan; Abadi, Ashraf H.
<x xml:space="preserve">Abstract</x> Herein, we report the synthesis of novel tetrahydro‐β‐carbolines that induce cell death via the autophagic pathway. Five of the new compounds induced cell death in a panel of patient‐derived human metastatic melanoma cells. The autophagic pathway was confirmed using LC3 autophagosome markers; the involvement of ATG7 and Beclin 1 autophagy regulating genes was confirmed using infection with short hairpin RNA (shRNA) to silence Beclin 1 and ATG7. Compound VIII (IC50 = 2.34–5.15 μM) displayed activities greater than cisplatin against a panel of patient‐derived human metastatic melanoma cell lines. The structure–activity relationship (SAR) of this class and the role of the absolute stereochemistry and geometrical isomerism are evaluated.